Succinate Is a Natural Suppressor of Antiviral Immune Response by Targeting MAVS - Xiao, Yue; Chen, Xinyi; Wang, Zhun; Quan, Jiazheng; Zhao, Xibao; Tang, Haimei; Wu, Han; Di, Qianqian; Wu, Zherui; Chen, Weilin (Frontiers in Immunology, 2022)
Succinate is at the crossroads of multiple metabolic pathways and plays a role in several immune responses acting as an inflammation signal. However, whether succinate regulates antiviral immune response remains unclear. Here, we found that the production of succinate was reduced in RAW264.7 cells during VSV infection. Using the diethyl succinate pretreated the mouse peritoneal macrophages and RAW264.7 cells before VSV infection, the production of interferon-β (IFN-β), chemokine (C-X-C motif) ligand 10 (CXCL-10) and IFN-stimulated genes 15 (ISG15) were significantly decreased; following, the VSV replication in diethyl succinate pretreated cells were obviously increased. Moreover, succinate decreased the expression of IFN-β in serum, lung and spleen derived from the VSV-infected mice. The overall survival rate in the VSV-infected mice with diethyl succinate-pretreatment was also remarkably downregulated. Furthermore, we identified that succinate inhibited the activation of MAVS-TBK1-IRF3 signaling by suppressing the formation of MAVS aggregates. Our findings provide previously unrecognized roles of succinate in antiviral immune response and establish a novel link between metabolism and innate immune response.